Caracterização tecnológica dos quartzo sienitos com hiperstênio butterfly beige e butterfly green - Bolonini, Thiago Motta [UNESP]; Godoy, Antonio Misson [UNESP] (My University, 2017)
The dimension stones studied are quartz syenites with hypersthene commercially known as Butterfly Beige and Butterfly Green, extracted in Barra de São Francisco-ES. The aim of this study, from the realization of technological characterization, is to help in the orientation of the possible uses of these lithotypes that present great petrographic similarity. The test results are generally within the standards for granite rocks, with the exception of Amsler wear (Butterfly Beige 2.19 mm, Butterfly Green 1.87 mm) and rupture modulus (dry Butterfly Green 8.03 MPa and 7.64 MPa after freezing and thawing; dry Butterfly Beige 4.07 MPa and 4.56 MPa after freezing and thawing), indicating the need for caution for use in high traffic and facade environments. On the other hand, they have values of porosity (Butterfly Beige 0.61%; Butterfly Green 0.52%) and water absorption (Butterfly Beige 0.23%; Butterfly Green 0.19%) that reflect safety to their applications in humid environments. In relation to the chemical attack, it is important to check the chemical composition of the cleaning agent to be used for maintenance and it is advisable to use only a moist cloth to clean it since the hydrochloric acid causes severe chromatic changes (Butterfly Green) and that citric acid caused the greatest loss of brightness in both rocks.
Technological characterization of butterfly beige and butterfly green quartz syenites with hypersthene
Keywords: Dimension stones; Geology; Technological characterization